1996
DOI: 10.1046/j.1537-2995.1996.36596282586.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of the human platelet antigen systems 1 through 5 by multiplex polymerase chain reaction and ligation‐based typing

Abstract: Multiplex polymerase chain reaction in combination with ligation-based typing allows fast typing of large numbers of platelet donors and screening for critical antigens in pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 21 publications
8
35
0
Order By: Relevance
“…28,34 GPIIb/IIIa is the final common pathway of activation signals generated by various stimuli and is a key molecule for platelet aggregation, thus being a recent target of antiplatelet therapy. However, because the PlA2 allele (the less frequent allele) is very rare in Japan 35 (our unpublished results indicated that PlA2 type is Ͻ1% in the normal Japanese), we did not include this polymorphism in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…28,34 GPIIb/IIIa is the final common pathway of activation signals generated by various stimuli and is a key molecule for platelet aggregation, thus being a recent target of antiplatelet therapy. However, because the PlA2 allele (the less frequent allele) is very rare in Japan 35 (our unpublished results indicated that PlA2 type is Ͻ1% in the normal Japanese), we did not include this polymorphism in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, complete agreement of the results was observed between this new approach including the allele-specific primers for both HPA-la and HPA-lb in a single PCR and the conventional HPA-1 genotyping performed in separate reactions and followed by gel electrophoresis. ternative strategies such as ligase chain reactions [9] of fered adequate specificity. Two groups [7,8] have recently demonstrated that a hot-start technique may enhance both the specificity and the efficiency of sequence-specific PCR for HPA typing.…”
Section: Detection Of the Pcr Products By Elisamentioning
confidence: 99%
“…Legier et al [9] have recently developed a method combin ing a multiplex PCR with ligation-based genotyping which offers genotyping of the platelet antigens HPA-1 to HPA-5 by detection of the reaction products by ELISA. In search of an efficient method for the screening of HPA-1 genotypes, we have evaluated the following approach.…”
Section: Introductionmentioning
confidence: 99%
“…2. The allele frequency for 163M is relatively low; for instance, it is 8.6% in the German population (16). In all cases, the PROBE primers were not fully extended, contrary to most PROBE reactions in solution.…”
Section: Resultsmentioning
confidence: 80%
“…ies may be involved (14)(15)(16). DNA fragments containing the polymorphic sites were amplified by the PCR.…”
Section: Resultsmentioning
confidence: 99%